Matrix Metalloproteinase–Driven Endochondral Fracture Union Proceeds Independently of Osteoclast Activity. (18th June 2013) - McDonald, Michelle M; Morse, Alyson; Mikulec, Kathy; Peacock, Lauren; Baldock, Paul A; Kostenuik, Paul J; Little, David G
ABSTRACT As new insights into the complexities of endochondral fracture repair emerge, the temporal role of osteoclast activity remains ambiguous. With numerous antiresorptive agents available to treat bone disease, understanding their impact on bone repair is vital. Further, in light of recent work suggesting osteoclast activity may not be necessary during early endochondral fracture union, we hypothesize instead a pivotal role of matrix metalloproteinase (MMP) secreting cells in driving this process. Although the role of MMPs in fracture healing has been examined, no directly comparative experiments exist. We examined a number of antiresorptive treatments to either block osteoclast activity, including the potent bisphosphonates zoledronic acid (ZA) and clodronate (CLOD), which work via differing mechanisms, or antagonize osteoclastogenesis with recombinant OPG (HuOPG‐Fc), comparing these directly to an inhibitor of MMP activity (MMI270). Endochondral ossification to union occurred normally in all antiresorptive groups. In contrast, MMP inhibition greatly impaired endochondral union, significantly delaying cartilage callus removal. MMP inhibition also produced smaller, denser hard calluses. Hard callus remodeling was, as expected, delayed with ZA, CLOD, and OPG treatment at 4 and 6 weeks, resulting in larger, more mineralized calluses at 6 weeks. As a result of reduced hard callus turnover, bone formation was reduced with antiresorptive agents at these time points. These results confirm that the achievement of endochondral fracture union occurs independently of osteoclast activity. Alternatively, MMP secretion by invading cells is obligatory to endochondral union. This study provides new insight into cellular contributions to bone repair and may abate concerns regarding antiresorptive therapies impeding initial fracture union.